Empowering Humanitarian Medical Development Using Grid Technology - Gonzales, J.; Pomel, S.; Breton, V.; Clot, B.; Gutknecht, J. L.; Irthum, B.; Legré, Y. (Methods of Information in Medicine, 2005)
Background: The training of local clinicians is the best way to raise the standard of medical knowledge in developing countries. This requires transferring skills, techniques and resources.Objectives: Grid technology opens new perspectives for preparation and follow-up of medical missions in developing countries as well as support to local medical centers in terms of teleconsulting, telediagnosis and patient follow-up. Indeed, grids allow to hide the complexity of handling distributed data in such a way that physicians will be able to access patient data while ignoring where these data are stored.Methods: To meet requirements of a development project of the French NPO Chain of Hope in China, we propose to deploy a grid-based federation of databases.First Results and Conclusions: A first protocol was established for describing the patients’ pathologies and their pre- and post-surgery states through a web interface in a language-independent way. This protocol was evaluated by French and Chinese clinicians during medical missions in the fall of 2003. The first sets of medical patients recorded in the databases will be used to evaluate grid implementation of services.
Keywords: Telemedicine; ehealth; grids; medical development; internet